"Ready" to "be visible": Wearing Hijab of Muslim women in Three Southern Border provinces of Thailand - Pollachom, Taweeluck (Journal of Social Sciences and Humanities Research in Asia, 2020)
This article study the decision to cover hijab of Muslim women who study secondary school before the Ministry of Education legislated the provisions of allowing school uniforms for Muslim students in Thai educational institution. This study found that the decision to wearing the hijab of these Muslim women had different patterns and periods. But there are similar factors that affect their decisions: growing up as an adult, spatial context with Islamic sensitivity and Islamic Religious dresses. Moreover, this study also found that family, friends and people around them, including religious knowledge, did not affect the decision to cover the hijab of Muslim women in this study. It was depends on their own "ready" or "not ready" decisions to path to religious life. That is not only about linking themselves with faith and religious rigor in everyday life, but it is "readiness" to bring themselves to being "visible" in public areas as Muslim women with reflections the performance of a "good Muslimah" that follow and submit with religious doctrine. Keywords: hijab, visibility, good Muslimah, the southern border provinces of Thailand